Implementasi Teknologi Biofilter sebagai Solusi Efisien dalam Menyediakan Air Bersih untuk Masyarakat di Desa Teluklada, Kecamatan Sobang, Kabupaten Pandeglang - Hidayat, Amat; Nuraida, Putri; Nuryati, Nuryati; Jalaludin, Muhammad; Yani, Ahmad; Abdul Majid, Mas Lutfi; Romadhon, Muhamad Rizki; Sakti, Prasyamsa Kusuma; Najib, Khaerun; Maulana, Sabil (Universitas Pahlawan Tuanku Tambusai, 2025)
The issue of clean water availability remains a significant challenge in rural areas, including Teluklada Village, Sobang District, Pandeglang Regency, where most residents rely on traditional water sources of poor quality. The water used by the community often has an unpleasant odor, turbidity, coarse particles, and mosquito larvae. The Community Service Program (KKM) 51 of Universitas Bina Bangsa, conducted from July 15 to August 7, 2025, aimed to implement biofilter technology as an appropriate solution to address this problem. This study is an applied research with a descriptive approach, utilizing direct observation, in-depth interviews, and brainstorming sessions with local residents and village officials. The implementation stages included site surveys, procurement of tools and materials, assembly, testing, and a result seminar. The biofilter employed natural filtration media consisting of activated carbon, silica sand, and coconut fiber, arranged vertically inside PVC pipes using a lateral-inlet-upflow system. The trial conducted at the KKM Post in Kampung Sadar RT 02/RW 02 showed a significant improvement in water quality: clearer appearance, reduced odor, absence of particles and larvae, and suitability for non-consumption purposes. Community response was highly positive, with requests for replication in other areas. However, limitations include the absence of laboratory testing for chemical and microbiological parameters and no trials on saline water sources. In conclusion, the biofilter technology proved to be effective, easy to construct, cost-efficient, and operable by the community independently, making it a potential model for sustainable clean water provision in rural areas.